Analisis Etika Bisnis Dalam Industri Keuangan Syariah di Indonesia - Najwa Azmi; Nur Shihatus Sakinah; Wafi Najmi Naufal Athallah; Dwi Novaria Misidawati (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze the implementation of business ethics in the Islamic financial industry in Indonesia, which is currently experiencing rapid development and has become an important component in the national financial system. This study uses a qualitative approach with a desk study method that reviews literature from official documents, scientific journals, and other relevant sources. The analysis was conducted descriptively-analytically by identifying, classifying, and synthesizing the literature to find patterns of ethical implementation and violations, as well as thematic comparisons between Islamic financial institutions. The results show that the application of business ethics not only reflects compliance with the prohibition of riba, gharar, and maysir, but also on the transparency of contracts, responsible management of customer funds, and commitment to corporate social responsibility (CSR) programs that support community empowerment and MSMEs. However, there are still challenges in the aspects of product transparency, ethical marketing practices, and risk management according to the principles of Islamic business ethics. This study emphasizes the need to implement stricter supervision and regulation so that business ethics practices can be implemented consistently. Thus, the Islamic finance industry can optimally contribute to inclusive and sustainable economic growth in Indonesia.